Correction: Impact of feralization on evolutionary trajectories in the genomes of feral cat island populations. - María Esther Nieto-Blázquez; Manuela Gómez-Suárez; Markus Pfenninger; Katrin Koch (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0308724.].